Gender inequality and its implications on education and health : a global perspective - Chakraborty, Chandrima; Pal, Dipyaman (Emerald Publishing Limited, 2023)
Gender inequality has wide-ranging and adverse implications for all of society. For this reason, the United Nations has made it a top priority to address this issue through the Sustainable Development Goals, which state that gender equality is not only a fundamental human right but a necessary foundation for a peaceful, prosperous, and sustainable world. Gender Inequality and its Implications on Education and Health explains the different implications of gender inequality and finds solutions to our most pressing issues. The authors of these collected studies show that though in various contexts around the globe, girls and women are discouraged and prevented from receiving quality education, proper health care, women empowerment and social justice, if this exclusion is eliminated it produces many additional socio-economic gains that benefit entire societies. Focusing largely on India to explore firstly the implications of gender inequality on education and health and then gender inequality and its implications to other SDGs, the chapters extend globally to analyse countries from Asia, Australia, Africa, and Europe. Raising awareness among stakeholders and institutions to recognise the importance of gender inequality throughout the world and its various implications - especially on education and health - Gender Inequality and its Implications on Education and Health provides strategies to achieve gender equality.